From the global risk society to the vulnerable society Towards a sociological analysis of the COVID-19 pandemic? (Revista de Investigaciones Universidad del Quindío, 2022)
The article sought to interpret the COVID-19 pandemic through the generalization of social vulnerability, converted into a sociological concept, as it was considered as a social fact caused by the crisis of the labor society, whose basis was the management of risks and dangers, through state welfare institutions, which later,  in the neoliberal economic model, it was individualized, diluting the state responsibility to attend to the dangers derived from the pandemic, exercising only its function of surveillance and control over individuals on the part of a neoliberal State, which ceased to consider them as citizens, defined by rights, which were protected with the existence of the welfare state.
Keywords: Global risk society; vulnerable society; pandemic; individualization